Kebijakan Pidana Kebiri Kimia Oleh Majelis Hakim Terhadap Pelaku Pemerkosaan Terhadap Anak di Indonesia - Enmo, M. Firza; Pohan, Masitah (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Chemical castration, medically known as "antiandrogen therapy", is a procedure that involves administering a chemical substance to suppress the production of the hormone testosterone. The aim is to reduce libido and erectile ability in men. Unlike physical castration, which is permanent, chemical castration is reversible, meaning that the effects will disappear once the treatment is stopped This study uses normative research methods, which are also referred to as legal research methods, positive legal research methods, doctrinal legal research methods, and pure legal research methods. Normative legal research is a type of research that centers on written law (law in books) or community customs. Most normative research data sources come from secondary data sourceschemical castration punishment can be considered contrary to several international human rights instruments that have been ratified by Indonesia.The Indonesian National Commission on Human Rights has also expressed its objection to the application of chemical castration punishment.The purpose of this study is expected to significantly reduce sexual crimes against children and provide better protection for the nation's future generations.The existence of castration punishment in Indonesia is a complex and multidimensional issue, involving legal, ethical, medical, social, and political aspects. Although intended as a decisive measure to protect children from sexual crimes, its implementation remains controversial and faces various practical and ethical challenges.